Atherogenic Index of Plasma Predicts Outcomes in Acute Ischemic Stroke - Liu, Hongbing; Liu, Kai; Pei, Lulu; Li, Shen; Zhao, Jiawei; Zhang, Ke; Zong, Ce; Zhao, Lu; Fang, Hui; Wu, Jun; Sun, Shilei; Song, Bo; et al. (Frontiers in Neurology, 2021)
Aim: The atherogenic index of plasma (AIP) was significantly related to adverse outcomes in patients with cardiovascular disease. Our aim was to investigate the association between AIP and adverse outcomes in acute ischemic stroke. Methods: Patients with acute ischemic stroke (AIS) admitted between 2015 and 2018 were prospectively enrolled in this study. Functional outcomes were evaluated by the modified Rankin Scale (mRS). Poor outcomes were defined as of mRS 3-6. The relationship of AIP with the risk of outcomes was analyzed by multivariate logistic regression models. Results: A total of 1463 patients with AIS within 24 hours of symptom onset were enrolled. The poor outcome group had a significantly higher level of AIP [0.09 (-0.10-0.27) vs. 0.04 (-0.09-0.18), P<0.001] compared with the good outcome group. Multivariable logistic regression analysis showed that higher AIP was associated with poor outcomes in all the stroke patients (OR 1.84, 95%CI, 1.23-2.53, P=0.007), which was more evident in patients with large-artery atherosclerosis subtype (OR 1.58, 95%CI, 1.32-1.87, P=0.021), but not in the other subtypes. Receiver operating curve (ROC) analysis revealed that the best predictive cut-off value of AIP was 0.112, with a sensitivity of 70.8% and a speciﬁcity of 59.2%. and the area under the ROC curves for AIP was 0.685. Conclusion: AIP may be an important and independent predictor of the outcome of dysfunction in patients with AIS, especially the stroke subtype of large-artery atherosclerosis.